Effectiveness of D-Mat on Improving Basic Jumping Motions in Early Children in Palembang - Dewi Septaliza; Noviria Sukmawati; Selvi Melianty; Selvi Atesya Kesumawati (UNIB Press, 2023)
Mastery of basic movements must start from an early age, because mastering basic movement abilities is an important foundation for children to be able to be involved in many kinds of physical activities in the future. This research is related to the basic motion of jumping. The aim of this study was to determine the effectiveness of D-Mat in increasing basic jumping motion in early childhood. This type of research is experimental research by providing treatment in the form of a game method with D- Mat in early childhood. The sample used in this study is the total number of early childhood children in early childhood education. The data were obtained from the results of the pretest and posttest. The research sample consisted of 4-5 years old children in TK Negeri Pembina 4 and TK Kurnia Makmur Palembang totaling 30 people. Data analysis techniques using the t test. Based on the results of the research based on the t-test calculation, the value of fcount <ftable or 4.29 <1.693 means that Ho is rejected and Ha is accepted. This shows that the child's final ability is better than before using the D-Mat. It can be concluded that D-Mat is effectively used to improve basic jumping motion in early childhood in Palembang. It is suggested that the D-Mat mat can be used in physical activities as well as learning because the D-Mat contains pictures of letters and numbers.